Candybots: CANDYBOTS: A New Generation of 3D‐Printed Sugar‐Based Transient Small‐Scale Robots (Adv. Mater. 52/2020). Issue 52 (28th December 2020) - Gervasoni, Simone; Terzopoulou, Anastasia; Franco, Carlos; Veciana, Andrea; Pedrini, Norman; Burri, Jan T.; de Marco, Carmela; Siringil, Erdem C.; Chen, Xiang‐Zhong; Nelson, Bradley J.; Puigmartí‐Luis, Josep; Pané, Salvador
Abstract : Have a CANDYBOT! Sugars are among the main sources of energy, and essential building blocks for all forms of life. In article number 2005652, Xiang‐Zhong Chen, Josep Puigmartí‐Luis, Salvador Pané, and co‐workers report the development of sugar‐based architectures via 3D printing. Because of their inherent degradability and biocompatibility characteristics, these structures have the potential to be applied in transient small‐scale robots.